2015
DOI: 10.3389/fnins.2015.00307
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging biomarkers for the early diagnosis of Alzheimer's disease: a machine learning approach

Abstract: Determination of sensitive and specific markers of very early AD progression is intended to aid researchers and clinicians to develop new treatments and monitor their effectiveness, as well as to lessen the time and cost of clinical trials. Magnetic Resonance (MR)-related biomarkers have been recently identified by the use of machine learning methods for the in vivo differential diagnosis of AD. However, the vast majority of neuroimaging papers investigating this topic are focused on the difference between AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
147
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(157 citation statements)
references
References 45 publications
7
147
1
2
Order By: Relevance
“…We also provide some citations showing the importance of corresponding brain regions. We can see that many of these selected brain regions are consistent with the observations reported in the previous literatures (Echávarri, et al, 2011; Jacobs, et al, 2012; Kosicek and Hecimovic, 2013; Salvatore, et al, 2015). For example, Echávarri et al (Echávarri, et al, 2011) have observed that parahippocampal gyrus and hippocampus are important biomarkers, while the former can discriminate better than the latter in terms of AD diagnosis.…”
Section: Resultssupporting
confidence: 91%
“…We also provide some citations showing the importance of corresponding brain regions. We can see that many of these selected brain regions are consistent with the observations reported in the previous literatures (Echávarri, et al, 2011; Jacobs, et al, 2012; Kosicek and Hecimovic, 2013; Salvatore, et al, 2015). For example, Echávarri et al (Echávarri, et al, 2011) have observed that parahippocampal gyrus and hippocampus are important biomarkers, while the former can discriminate better than the latter in terms of AD diagnosis.…”
Section: Resultssupporting
confidence: 91%
“…Multiple studies have found structural MRI (sMRI), a useful diagnostic tool that can contribute to detecting AD-related modifications before the development of clinical symptoms (Raskin et al 2015;Xie et al 2015;Teipel et al 2015;Besson et al 2015;Goveas et al 2015). A different way in which sMRI can assist in early AD diagnosis is by providing data sets for a distinct group of recently developed analytical procedures involving advanced mathematical and statistical methods such as machine learning (Gorji and Haddadnia 2015;Klöppel et al 2008;Salvatore et al 2015;Zhan et al 2015) and graph theory, the formal study of networks (Supekar et al 2008;Stam et al 2009;He et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Short runs emphasis, Long runs emphasis, Graylevel non-uniformity, Run-length non-uniformity, Run percentage [78], [83]- [85] D. Classification methods Classification is used for the identification of patterns features of interest into the classes they belong. Moreover, machine-learning techniques have the potential to classify MR features without requiring a priori hypotheses from where this information may be coded in the images [86]. When classifiers are used, image samples are divided into two sets, training and testing [87].…”
Section: B Region Of Interest / Segmentationmentioning
confidence: 99%